The effects of large-scale social restriction during the covid-19 pandemic on glycemic control and occurrence of complications in children with type-1 diabetes mellitus - Sahara Effendy; Setya Wandita; Madarina Julia (Paediatrica Indonesiana, 2023)
Background The global pandemic of severe acute respiratory syndrome caused by the coronavirus-2 (SARS-CoV-2) infection has resulted in a national large-scale social restriction (LSSR) to limit the spread of the virus. Objective To determine the impacts of LSSR on glycemic controls and the occurrence of complications in type-1 diabetes mellitus (T1DM) children. Methods A retrospective longitudinal study was carried out in Dr. Sardjito Hospital, Yogyakarta. Subjects were 0-18 years old T1DM patients diagnosed before the LSSR with at least six months of disease. Data on demographics, T1DM status, HbA1c level, and complications pre-LSSR, and during LSSR were taken from medical records. Paired T-tests were used to assess the difference in HbA1c level between the two-time points Results: We included information on 21 children based on the inclusion and exclusion criteria. Their median (range) age was 13.9 (1.42-17.3) years, with a median (range) diabetes duration of 2.6 (0.0-10.92) years. Glycemic control improved in 76% of the children. The mean HbA1c before and during LSSR was 10.9 (SD 2.7) and. 9.7 (SD 2.3), respectively; P<0.05. The glycemic control was not associated with sex, age, duration of diabetes, travel time to the clinic, or a total daily insulin dose. There was also no significant difference in the occurrence of complications. Conclusion Despite limitations during LSSR, glycemic control improved in most patients with T1DM. This might be related to improved health awareness during the pandemic, more regular meals, and better parental control.